Day Of The Beast - Grey, Zane
Ever since the day he was deployed to fight in WWI, Daren Lane dreamed of the day that he returned home. Feeling that it had been several years since he left, Daren finally returns home to America, but soon realizes that it is not the home he remembers. Others have been able to move on from the war, causing Daren to question if his sacrifice of service was even worth it. Though he is attached to the ideals and behavior popular during the Victorian era, the rest of American society have moved on to the frivolous and fun attitude of the roaring twenties. When Daren notices that his younger sister is participating in this culture, drinking underage, gambling, and taking drugs, Daren is repulsed. Feeling that it is immoral and irreverent, he vows to put a stop to it. While organizing a way to combat his community$1 (Bs declining morals, the young soldier receives a troubling diagnosis due to an injury that he sustained during the war. While coming to terms with this discovery, Daren decides to dedicate his time to mentoring the youth, attempting to reform their behavior. With themes of cultural and generational divides, The Day of the Beast by Zane Grey is a somber and intriguing narrative that depicts a soldier$1 (Bs complicated integration back into civilian life. Written with descriptive and moving prose, The Day of the Beast is emotional and provides a unique and rare perspective on the cultural change of the roaring twenties. Adding to the fascinating discussions of this historic period, this Zane Grey masterpiece is captivating and relevant to a modern audience. This edition of The Day of the Beast by Zane Grey now features a new, eye-catching cover design and is printed in a font that is both modern and readable. With these accommodations, this edition of The Day of the Beast crafts an accessible and pleasant reading experience for modern audiences while restoring the original drama and depth of Zane Grey$1 (Bs work. s
63767
Keywords: Disabled veterans; Social change; American fiction -- 20th century; Western